EVALUASI PELAKSANAAN PROGRAM AKSELERASI PADA SEKOLAH MENENGAH PERTAMA DAN MADRASAH TSANAWIYAH - Mutasim, Imam (FKIP Universitas Wisnuwardhana, 2018)
This focus of research are as follows: 1) how does the readiness of resources at the input stage in the implementation of an accelerated program?, 2) how is the effectiveness of the learning at this stage of the process in the implementation of an accelerated program ?, 3) how is the success achieved in phase outputs and outcomes in the implementation of an accelerated program?, 4) What are the constraints faced in the implementation of an accelerated program?, 5) how is the follow-up evaluation results for program improvement acceleration? This study used a qualitative approach to the design of multi-case, because the two cases studies with different backgrounds. Â From the results of the research data exposure in State Junior High School 3 of Malang, Laboratory Junior High School P of State University of Malang, and State Islamic junior high school 3 of Gondanglegi found as follows: First resource ofÂ accelerated program implementations: 1) the Establishment of a team through meetings of teachers and principals, 2) the appointmentÂ homeroom and acceleration teacher, 3) teachers acceleration met the requirements specified qualification standards both the competence and professionalism teachers acceleration, 4) teachers were given training acceleration, 5) teachers accelerated classes participated in the subject teachers Council inter-school organizer accelerated classes in Malang City, 6) mentoring new teachers who the first teaching in the classroom acceleration by the senior teachers of acceleration, 7) monitoring and supervision to the acceleration teachers by the team and the principal.Keywords: program evaluation, acceleration class, junior high school, islamic junior high school